2011
DOI: 10.1002/jctb.2604
|View full text |Cite
|
Sign up to set email alerts
|

Different process configurations for bioethanol production from pretreated olive pruning biomass

Abstract: BACKGROUND: In Mediterranean countries, olive tree pruning provides a widely available renewable agricultural residue with, currently, no industrial application. This residue could provide feedstock for the bioethanol industry. In the present study, olive tree pruning biomass pretreated with both 'liquid hot water' and 'dilute-sulfuric acid' was tested as a substrate for ethanol production. Three different process configurations, separate hydrolysis and fermentation (SHF), simultaneous saccharification, fermen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
1
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 35 publications
7
31
1
1
Order By: Relevance
“…The enzymatic presaccharification yield decreased with increasing substrate loadings (constant enzyme to substrate ratio), obtaining the lowest yield value (53.7%) at 25% (w/w) (Table 1). These results are in line with others reported on different steam‐exploded lignocellulosic substrates 34–36. The mechanism behind the decreasing conversion has been attributed to different factors, including end‐product inhibition or inhibition by degradation products, changes in substrate reactivity during enzymatic hydrolysis, mass transfer limitations, and unproductive adsorption of enzymes 14, 33.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The enzymatic presaccharification yield decreased with increasing substrate loadings (constant enzyme to substrate ratio), obtaining the lowest yield value (53.7%) at 25% (w/w) (Table 1). These results are in line with others reported on different steam‐exploded lignocellulosic substrates 34–36. The mechanism behind the decreasing conversion has been attributed to different factors, including end‐product inhibition or inhibition by degradation products, changes in substrate reactivity during enzymatic hydrolysis, mass transfer limitations, and unproductive adsorption of enzymes 14, 33.…”
Section: Resultssupporting
confidence: 91%
“…Enzymatic presaccharification of WIS with the standard NS50013/NS50010 enzyme mixture resulted in higher glucose concentrations as the substrate loadings increased (Table 1), obtaining the highest glucose concentration (100.5 g L −1 ) at 25% (w/w). In all the loadings assayed, the major degree of glucan conversion was achieved within the first 24 h of the enzymatic presaccharification (Table 1), in accordance with previous studies 33, 34. Only at a substrate loading of 25% (w/w), an increase of glucose production was observed from 24 to 48 h of hydrolysis (Table 1).…”
Section: Resultssupporting
confidence: 90%
“…Same enhancement in ethanol production efficiency was also demonstrated by Kim et al [25], who observed an increase in ethanol yield from 0.31 g/g to 0.43 g/g total solid when applying a Separate Hydrolysis and Fermentation (SHF) process instead of Simultaneous Saccharification and Fermantation (SSF) process on cafeteria food waste. Manzanares et al [29] also found that with increasing initial DM content, a separate saccharification step improves fermentation of liquid hot waterpretreated olive-pruning biomass. Finally, Hoyer et al [30] reported that with increasing DM content, even 4 h of saccharification could significantly improve fermentation of softwoods.…”
Section: Resultsmentioning
confidence: 96%
“…The highest ethanol concentration at 72 h SSF were 68.28 g/L (A) and 78.25 g/L (B).According to literature, the threshold of economic profitability corresponds to bioethanol concentrations in the fermentation broth in the range 4-5 volume percent. Achieving this threshold entails the utilization of media containing 15-20% solids (on dry basis) [28]. Therefore, increasing substrate loading required to produce high-concentration ethanol so that the process is more profitable.…”
Section: Effect Of Variation Of Substrate Concentration Loading Direcmentioning
confidence: 99%